Nudging in Animal Disease Control and Surveillance: A Qualitative Approach to Identify Strategies Used to Improve Compliance With Animal Health Policies - Garza, Maria; Ågren, Estelle C. C.; Lindberg, Ann (Frontiers in Veterinary Science, 2020)
Professionals from seven European countries were interviewed to identify strategies used in surveillance and control of animal infections to influence behaviours such as programme enrolment, adoption of biosecurity measures, and engagement in surveillance. To find strategies that were well-designed from a theoretical perspective, three theoretical frameworks from nudge theory was were applied to the strategies; the Nuffield ladder to determine the strength of the interventions, EAST; to identify attributes of the strategies and, and MINDSPACE, to identify psychological mechanisms involved. We found that almost two thirds (91/120) of the strategies were designed in a manner likely to trigger multiple psychological mechanisms, which is in line with existing recommendations for successful effect i.e. achieving a desired behaviour. This was despite that the design of the strategies were based on professionals empirical understanding of requirements to achieve anticipated outcomes, rather than systematic use of methods from behavioural sciences and psychology. The most commonly used strategy was provision of information, and the least used mechanism was making a desired behaviour easy to perform. The findings in this study, with all the examples of strategies used, can serve as inspiration for others. The theoretical frameworks may also be beneficial to apply as a complement in future design of new strategies. This study did not include evaluation of how efficient different strategies have been, which would be an interesting area for future studies.